Antidiabetic Medicinal Plants Used in Democratic Republic of Congo: A Critical Review of Ethnopharmacology and Bioactivity Data - Kasali, Félicien Mushagalusa; Kadima, Justin Ntokamunda; Peter, Emanuel L.; Mtewa, Andrew G.; Ajayi, Clement Olusoji; Tusiimire, Jonans; Tolo, Casim Umba; Ogwang, Patrick Engeu; Weisheit, Anke; Agaba, Amon Ganafa (Frontiers in Pharmacology, 2021)
Several studies have been conducted and published on medicinal plants used to manage Diabetes Mellitus worldwide. It is of great interest to review available studies from a country or a region to resort to similarities/discrepancies and data quality. Here, we examined data related to ethnopharmacology and bioactivity of antidiabetic plants used in the Democratic Republic of Congo. Data were extracted from Google Scholar, Medline/PubMed, Scopus, ScienceDirect, the Wiley Online Library, Web of Science, and other documents focusing on ethnopharmacology, pharmacology, and phytochemistry antidiabetic plants used in the Democratic Republic of Congo from 2005 to September 2021. The Kew Botanic Royal Garden and Plants of the World Online web databases were consulted to verify the taxonomic information. CAMARADES checklist was used to assess the quality of animal studies and Jadad scores for clinical trials. In total, 213 plant species belonging to 72 botanical families were reported. Only one plant, Droogmansia munamensis, is typically native to the DRC flora; 117 species are growing in the DRC and neighboring countries; 31 species are either introduced from other regions, and 64 are not specified. Alongside the treatment of Diabetes, about 78.13% of plants have multiple therapeutic uses, depending on the study sites. Experimental studies explored the antidiabetic activity of 133 plants, mainly in mice, rats, guinea pigs, and rabbits. Several chemical classes of antidiabetic compounds isolated from 67 plant species have been documented. Rare phase II clinical trials have been conducted. Critical issues included poor quality methodological protocols, author name incorrectly written (16.16%) or absent (14.25%) or confused with a synonym (4.69%), family name revised (17.26%) or missing (1.10%), voucher number not available 336(92.05%), ecological information not reported (49.59%). Most plant species have been identified and authenticated (89.32%). Hundreds of plants are used to treat Diabetes by traditional healers in DRC. However, most plants are not exclusively native to the local flora and have multiple therapeutic uses. The analysis showed the scarcity or absence of high-quality, in-depth pharmacological studies. There is a need to conduct further studies of locally specific species to fill the gap before their introduction into the national pharmacopeia.